Protective effect of injectable iron on cadmium-induced anemia in rats - Ghada Taqa; Jawnaa Mamdoh (College of Education for Pure Sciences, 2009)
Abstract The current paper studied, the protective effect of iron on anemia induced by Cadmium (Cd). Fifteen male albino rats selected in this study divided into three groups, first group as control, 2nd and 3rd groups received oral CdCl2 25mg /L mixed with drinking water for one month. Third group treated four dosage of injected iron (iron Dextran) at 50 mg/kg intraperitonially in addition to cadmium drinking water. The result of this study showed a significant decreased of iron concentration in plasma of Cd treated group but there is a significant increase in iron concentration in 3rd group compared to 2nd group p < 0.05 while there is a significant elevated with alanine aminotransferase enzyme in 2nd and 3rd group in comparing to control group. Alkaline phosphatase enzyme no change. Conclusions: this study concluded that iron supplement is prevent anemia induced by long exposure to cadmium.